التعامل مع السجناء وفق المعايير الدولية ومقارنته بقانون السجون الجزائري - شريك, مصطفى (Sciences de l'Homme et de la Société; Vol. 11 (2014): SCIENCES DE L'HOMME ET DE LA SOCIÉTÉ)
في الدراسة الحالية نحاول بحث آلية التعامل مع السجناء داخل المؤسسات العقابية، من خلال قراءة تجربة السجون الجزائرية في تأهيل النزلاء والتكفل بهم، والسعي لإعادة إدماجهم الاجتماعي، وحتى تكون الدراسة الحالية قادرة على استجلاء هذه التجربة كان لابد من الاعتماد على طريقة المقاربة مع المعايير الدولية في التعامل لكي تكون المحاولة أكثر قربا إلى الموضوعية في الطرح، والعلمية في القصد، وطبيعي جدا أن آلية التعامل تفيد في التعرف على مدى تحقيق الأهداف الإصلاحية المرجوة من عملية التأهيل في تنمية شخصية السجين، وتعديل سلوكياتها نحو القيم الفضيلة والسامية، وهو ما سنركز عليه في جوانب عملية التكفل بالسجناء اجتماعيا ونفسيا وصحيا وتربويا، وتأهيلهم علميا ومهنيا، وتهذيبهم أخلاقيا.   In the present study we try to search mechanism for dealing with prisoners in penal institutions, by reading the experience of Algerian prisons in the rehabilitation of inmates and provide for them, the pursuit of social reintegration, and even the current study is able to clarify this experiment it was necessary to rely on the method of approach with international standards in deal to be trying closer to objectivity in the subtraction, and scientific in intent, very natural that the mechanism for dealing serve to identify the extent to which the objectives of the reform desired by the rehabilitation process in the development of personal prisoner, and modify their behaviors towards the values of virtue and the High Commissioner, which we will focus in the aspects of process ensure prisoners socially and psychologically healthy and educationally, and rehabilitation of scientifically and professionally and morally.